Nuisance Growth of Cissus verticillata (Vitaceae) Negatively Affects the Structure of Mangroves in Marismas Nacionales Nayarit, Mexico - Olivia Millán-Aguilar; María Luisa Ordóñez-Rosas; Isaac Castillo-Cruz; Lidia Rodríguez-Arredondo; Marcelino Ruiz-Domínguez; Miguel Ángel Hurtado-Oliva; Marlenne Manzano-Sarabia (Diversity, 2025)
Changes in the structure and composition of mangroves may be influenced by anthropogenic and natural causes. Mangrove coverage in Marismas Nacionales Nayarit –a Biosphere Reserve in northwestern Mexico—has declined in the last decades, mostly related to human activities (e.g., opening of the Cuautla inlet) and climate variability (e.g., El Niño Southern Oscillation and hurricanes), leading to diverse ecological and socioeconomic consequences. This contribution reports the impact of Cissus verticillata—a climbing plant species—in the structure of mangroves distributed in this Natural Protected Area during 2019 and 2022. Forest structure analysis was compared in four plots of 20 m × 20 m each, all of them influenced by San Pedro Mezquital river. Two plots (Unión de Corrientes) showed the presence of Cissus verticillata, while two nearby plots (Boca de Camichín) recorded no presence of this species. A poor mangrove structure, no natural seedling recruitment and high mortality was observed in those sites with the presence of C. verticillata. These results highlight the vulnerability of mangroves to C. verticillata in Marismas Nacionales Nayarit Biosphere Reserve, which in addition to other human and climate stressors may compromise its ecological integrity in the future.